Pembelajaran Tari Topeng Mochi Melalui Metode Mind Mapping Untuk Meningkatkan Pemahaman Budaya - Riana Rosa Prastika; Juju Masunah; Tati Narawati (Gondang: Jurnal Seni dan Budaya, 2021)
This study aims to improve the ability to understand culture through the Mochi Mask dance. The research method used experimental. The research sample of students of the Sagara dance studio, Sukabumi city. Data collection techniques using a questionnaire. Data analysis techniques using nonparametric statistics. Mochi mask is a type of dance that develops in the city of Sukabumi. This dance is inspired by the culinary culture of the city of Sukabumi, namely Mochi. Sanggar Sagara is one that provides material for Mochi Mask dance using the Mind Mapping method. This method is a treatment to improve the ability to understand culture. The results showed an increase in the ability to understand culture. This is indicated by the average pretest results of 66.00. and the post test results of 87.50. Based on the research results, it can be concluded that the mind mapping method can improve the ability to understand culture. It is suggested that other studios can use the mind mapping method to improve their ability to understand culture.